2013
DOI: 10.1021/jf4029859
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Cadmium Transfer from Soil to Carrot (Daucus carota L.) and Its Application To Derive Soil Thresholds for Food Safety

Abstract: At present, soil quality standards used for agriculture do not fully consider the influence of soil properties on cadmium (Cd) uptake by crops. This study aimed to develop prediction models for Cd transfer from a wide range of Chinese soils to carrot (Daucus carota L.) using soil properties and the total or available soil Cd content. Path analysis showed soil pH and organic carbon (OC) content were the two most significant properties exhibiting direct effects on Cd uptake factor (ratio of Cd concentration in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…As this survey was done across a wide range of different locations it is expected that the soil properties, which affect the availability and uptake of metals from soils, will be different at different sites. Soil pH has been identified as an important factor in cadmium accumulation in plants (Adams et al, 2004;Zheng et al, 2011;Zhao et al, 2010;Ding et al, 2013Liu et al, 2015. For example, Liu et al (2015) demonstrated that wheat varieties accumulated more cadmium in acidic soils compared to alkaline soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this survey was done across a wide range of different locations it is expected that the soil properties, which affect the availability and uptake of metals from soils, will be different at different sites. Soil pH has been identified as an important factor in cadmium accumulation in plants (Adams et al, 2004;Zheng et al, 2011;Zhao et al, 2010;Ding et al, 2013Liu et al, 2015. For example, Liu et al (2015) demonstrated that wheat varieties accumulated more cadmium in acidic soils compared to alkaline soils.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al (2015) demonstrated that wheat varieties accumulated more cadmium in acidic soils compared to alkaline soils. Other important soil factors include organic carbon content, cation exchange capacity, and clay content, as well as the oxide content of Fe, Al, and Mn (Zheng et al, 2011;Zhao et al, 2010;Ding et al, 2013;). As these factors would vary across the different sampling locations, this may be a reason for the lack of correlations between soil and plant heavy metal concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The direct cause-and-effect relationships between environmental factors and vegetables accumulating Cd from soil are difficult to determine because environmental factors are often correlated (Basta et al, 1993;Ding et al, 2013). By partitioning the correlation coefficient into direct and indirect effects, the path model (PA) can be used to determine the causal relationship in the agronomic studies (Shipley, 2009).…”
Section: Path Analysis Modelmentioning
confidence: 99%
“…The direct effects of environmental variables on PUF are termed path coefficients and derived from multiple regression of environmental variables on PUF (Basta et al, 1993). Indirect effects are determined from the product of a simple correlation coefficient between environmental factors and the path coefficients (Ding et al, 2013). The relations between the correlation coefficient, direct effect and indirect effect are described in the following function:…”
Section: Path Analysis Modelmentioning
confidence: 99%
See 1 more Smart Citation